PENGARUH MOTIVASI KERJA DAN LINGKUNGAN KERJA TERHADAP KEPUASAN KERJA KARYAWAN PADA PABRIK PT. EKA DURA INDONESIA (Palm Oil Mill) ROKAN HULU - Wansyahdio, Hasnur; ", Kasmiruddin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
This research intent to know job motivation influence and work condition to job satisfaction fires an employee on plant wide PT. Eka Dura Indonesia. Where is proposed two variable free and one variable be tied-up, which is job motivation and variable personation work condition frees and variable personation job satisfaction be tied-up.Population in observational it is fire an employee on plant wide PT. Eka Dura is Indonesia, with total sample take 66 person with slovin's formula. Seeking procedure to be done bases accidental sampling. Observational data as data of primary, with questionnaire as instrument research, analisis is data that is utilized is with analisis statistic with help programs SPSS.analisis's result utilize bifilar linear regression, quiz t, and quiz f so gets to be known that variable motivates job and signifikan's ascendant work condition to job satisfaction fires an employee (H1), that influential job motivation signifikan to job satisfaction fires an employee (H2), and signifikan's ascendant work condition to job satisfaction fires an employee (H3).Key word : Job motivation, Work condition, and job satisfaction